Contemplation and action: Christian and Islamic spirituality in dialogue - Syafa’atun Almirzanah (HTS Teologiese Studies/Theological Studies, 2023)
Prayer, meditation and contemplation have long been established as essentials in human life all over the world. Yet, even by a religious devotee, they are regarded in one way or another as insignificant and secondary: what is taken into accounts is just getting things done. Thus, prayer sounds simply as ‘saying words’, and meditation is an obscure and complicated practice not easily understood. Even if there is any advantage, it is recognised and perceived as totally detached from the life of average people. Contemplative life is indeed sometimes seen as something sceptical. The article challenges the perspective and saying that the absolute principle of prayer is intensifying intimate accomplishment in love, the awareness of God. The authentic goal of meditation is the search and discovery of advanced dimensions in freedom, illumination and love, in intensifying our awareness of our life in God. Besides, people usually consider contemplative life as the opposite of active life and prefer to contemplative life. Using one of the greatest Catholic mystic’s perspective, the article shows that contemplative life is not better than active and not vice versa. Both are necessary. In this case, the article also put into a dialogue with Islamic spirituality.